Extracellular Matrix Stiffness Regulates DNA Methylation by PKCα‐Dependent Nuclear Transport of DNMT3L (Adv. Healthcare Mater. 16/2021). Issue 16 (17th August 2021) - Zhao, Xin‐Bin; Chen, Yun‐Ping; Tan, Min; Zhao, Lan; Zhai, Yuan‐Yuan; Sun, Yan‐Ling; Gong, Yan; Feng, Xi‐Qiao; Du, Jing; Fan, Yu‐Bo
Abstract : Extracellular Matrix Stiffness In article number 2100821 by Jing Du, Yu‐Bo Fan, and co‐workers, extracellular matrix (ECM) stiffness has profound effects on the regulation of cell functions. Stiff ECM enhances DNA methylation of pluripotent genes by the nuclear transport of DNA methyltransferase 3‐like binding to Nanog promoter in mouse embryonic stem cells (mESCs). DNA methylation is a novel target for the mechanical sensing mechanism during mESCs–ECM interactions.